Development of Problem-Based Learning (PBL)-Based Digital Books (E-Books): Public Administration at SMK NU Lamongan - Diyah Arum; Siti Sri Wulandari (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
This paper discusses the e-book development process based on Problem-based Learning in public administration learning material, produces and tests product feasibility, and finds out students’ responses to e-book development. The type of research is RnD (Research and Development) with IDI procedural type method (Instructional, Development, Institute), which consists of three stages, namely define, develop, and evaluation stages. Research data are e-book development and e-book quality acquisition through validation sheets and students’ questionnaire responses. The product validation stage is carried out by design experts, material experts, and linguists by giving a score of 0-100 while the students’ questionnaire responses are interviews. The average of assessment results from validation sheets by design experts is 73,25%, which means valid and feasible. The average score of material experts is 83,12%, which means valid and feasible. The average score from linguists is 92,25%, which means very feasible. Thus, the final score of the three validations is 84,3%. It can be concluded that the use of e-books is valid and feasible. It is reinforced by the results of the students’ questionnaire response questionnaire results indicated an average score of 93.5%, which means that the digital book is valid and feasible to use.